2009
DOI: 10.1002/jmv.21501
|View full text |Cite
|
Sign up to set email alerts
|

Specific mutations in the enhancer II/core promoter/precore regions of hepatitis B virus subgenotype C2 in Korean patients with hepatocellular carcinoma

Abstract: Recently, hepatitis B virus (HBV) genotypes and mutations have been reported to be related to hepatocellular carcinoma (HCC). This cross-sectional case-control study examined the relationship between HCC and mutations in the enhancer II/core promoter and precore regions of HBV by comparing 135 Korean HCC patients infected with HBV genotype C2 (HBV/C2; HCC group) with 135 age-, sex-, and hepatitis B e antigen (HBeAg) status-matched patients without HCC (non- HCC group). Age and sex were also matched between HBe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 46 publications
6
36
0
Order By: Relevance
“…To our knowledge, the current case-control study is the first to reveal the association between HBV mutations and the development of HCC among Thai patients. In this study, we found that double A1762T/G1764A mutations were an independent risk factor for the development of HCC, which was consistent with recent casecontrol studies conducted in China, Taiwan, and Korea [7,12,20,21]. Also, the magnitude of the OR of HCC associated with the presence of the BCP double mutants in this study was approximately 3 to 4-fold, which was similar with reports of other studies.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, the current case-control study is the first to reveal the association between HBV mutations and the development of HCC among Thai patients. In this study, we found that double A1762T/G1764A mutations were an independent risk factor for the development of HCC, which was consistent with recent casecontrol studies conducted in China, Taiwan, and Korea [7,12,20,21]. Also, the magnitude of the OR of HCC associated with the presence of the BCP double mutants in this study was approximately 3 to 4-fold, which was similar with reports of other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Although the region nts 1613 to 1764 in the X gene and nts 1899 to 2203 in the pre-C/C gene constitute only 14.2% of the HBV genome, they contained 75.0% (9 of 12) of the mutations showing a significantly higher frequency in HCC patients from the full-length HBV sequence analysis (Table 2). Among the four HCC-related mutations in the X gene, C1653T, A1762T, and G1764A have been studied extensively (3,(12)(13)(14)(15)(16), whereas G1613A is less well defined. G1613A was first reported by Takahashi et al, who noted that, of 40 HCC tissue samples tested, 15 contained this type of mutation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence have shown that an HBV strain with a complex mutation pattern rather than a single mutation was associated with a higher risk for advanced liver disease. These combinations included C1653T plus A1762T/ G1764A (14), A1762T/G1764A plus C1766T and/or T1768A (12), pre-S deletion plus A1762T/G1764A (5), and deletions in BCP plus C and/or pre-S (32). Those cross-sectional studies provided little information on the evolution of the HBV sequence during HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, genotypes B and C are apparently aggressive with respect to the development of HCC. However, in South Korea, nearly all HBV cases are genotype C2 (Ce) [28][29][30][31][32][33] . Although highly prevalent in HCC (86%), the prevalence of the precore stop mutation does not differ significantly among chronic HBV carriers with or without HCC [32,34,35] .…”
Section: Mutationmentioning
confidence: 99%
“…However, in South Korea, nearly all HBV cases are genotype C2 (Ce) [28][29][30][31][32][33] . Although highly prevalent in HCC (86%), the prevalence of the precore stop mutation does not differ significantly among chronic HBV carriers with or without HCC [32,34,35] . Most isolates of HBV genotype C2 in South Korea carry the T1858 mutation [32,33] , which attenuates the stability of the secondary structure of the pregenome encapsidation signal (epsilon signal).…”
Section: Mutationmentioning
confidence: 99%